2021
DOI: 10.3390/jcm10040555
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Prognosis of Ventilator-Associated Pneumonia in Critically Ill Patients with COVID-19: A Multicenter Study

Abstract: The primary objective of this multicenter, observational, retrospective study was to assess the incidence rate of ventilator-associated pneumonia (VAP) in coronavirus disease 2019 (COVID-19) patients in intensive care units (ICU). The secondary objective was to assess predictors of 30-day case-fatality of VAP. From 15 February to 15 May 2020, 586 COVID-19 patients were admitted to the participating ICU. Of them, 171 developed VAP (29%) and were included in the study. The incidence rate of VAP was of 18 events … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
94
4
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(114 citation statements)
references
References 31 publications
6
94
4
10
Order By: Relevance
“…Eleven of the included studies reported data on mortality in patients with COVID-19 and VAP [ 9 , 15 , 16 , 20 , 21 , 23 , 24 , 25 , 30 , 31 , 32 ]. The pooled estimated occurrence of mortality (at the longest available follow-up) was 42.7% (95% C.I.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Eleven of the included studies reported data on mortality in patients with COVID-19 and VAP [ 9 , 15 , 16 , 20 , 21 , 23 , 24 , 25 , 30 , 31 , 32 ]. The pooled estimated occurrence of mortality (at the longest available follow-up) was 42.7% (95% C.I.…”
Section: Resultsmentioning
confidence: 99%
“…The severity of lung damage in patients with COVID-19 pneumonia may lead to an increase in the rate of infections. Furthermore, patients with COVID-19 frequently needed prolonged mechanical ventilation, prone positioning [ 1 ] and received immunomodulant therapies, that may have increased their risk of developing VAP [ 9 ]. On the other hand, the ICUs may have been overcrowded in the period of peak of COVID-19 pandemic, with a possibly inadequate staffing (e.g., nurse to patient ratio) and more episodes of cross-contaminations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…( 22 ) S. aureus has been reported as a frequently-isolated organism from deep respiratory specimens taken from critically-ill COVID-19 patients with VAP. ( 23 ).…”
Section: Covid-19 and Antibiotic-resistant Healthcare-associated Infectionsmentioning
confidence: 99%